The Effect of Quality of Work Life, Organizational Culture and Job Satisfaction on Employee Engagement - Natasya, Nadya Shepti; Awaluddin, Robi (LPPM Universitas Bina Bangsa, 2021)
This study aimed to examine and analyze the effect of quality of work-life, organizational culture and job satisfaction on employee engagement with employees of CV. Surya Nedika Isabella. The cause of the decline in employee performance is due to lack of job satisfaction and the lack of support for the work environment in the company so that employees feel less comfortable. The method used in this research is the quantitative method with a descriptive approach. The population in this study were all employees of CV. Surya Nedika Isabella, totaling 90 people. Data were collected by questionnaires that have been tested for validity and reliability. The data analysis technique used was the multiple linear regression method with the saturated sampling technique. The data collection technique used is a questionnaire/questionnaire. The results of this study are the quality of work-life has a significant effect on employee engagement, organizational culture has a substantial impact on employee engagement, job satisfaction has a significant impact on employee engagement, quality of work-life, organizational culture and job satisfaction has a significant effect on employee engagement